Hyperthermia-induced in situ drug amorphization by superparamagnetic nanoparticles in oral dosage forms - Ansari, Shaquib Rahman; Teleki, Alexandra; Asad, Shno; Hempel, Nele-Johanna; Svedlindh, Peter; Lobmann, Korbinian; Bergström, Christel AS (Uppsala University, 2022)
Superparamagnetic iron oxide nanoparticles (SPIONs)
generate heat upon exposure to an alternating magnetic field (AMF) which has
been studied for hyperthermia treatment and triggered drug release. This study
introduces a novel application of magnetic hyperthermia to induce amorphization
of a poorly aqueous soluble drug, celecoxib, in situ in tablets for oral administration. In situ
amorphization can overcome the drug development hurdle of poor aqueous
solubility by molecularly dispersing the drug in a polymeric network inside a
tablet. However, current shortcomings of this approach include low drug loading
in the tablets, toxicity of enabling excipients, and drug degradation. Here,
SPIONs produced by flame spray pyrolysis are compacted with polyvinylpyrolidone
and celecoxib, and exposed to an AMF. The degree of amorphization is strongly
linked to the maximum tablet temperature achieved during AMF exposure, which
depends on SPION composition and content in the tablets. Manganese ferrites
exhibit no toxicity in human intestinal Caco-2 cell lines and are more
effective than zinc ferrites in inducing complete amorphization of celecoxib.
The resulting rapid dissolution and high solubility of in situ amorphized celecoxib in biorelevant intestinal fluid
demonstrates the promising capability of SPIONs as enabling excipients to
magnetically induce amorphization in
situ in oral dosage forms.
Keywords: Pharmaceutical sciences; Nanomaterials; Medical and Health Sciences; Medicin och hälsovetenskap; Nanotechnology for Materials Science; Nanoteknisk materialvetenskap; Pharmaceutical Sciences; Farmaceutiska vetenskaper